Learning and teaching experience-therapeutic touch for woman during labour - Silveira, Isolda Pereira da; Barroso, Maria Grasiela Teixeira; Silva, Raimunda Magalhães da (Rev Rene, 2002)
This is a report of learning and teaching experience of therapeutic touch for women before before and during labour. A class was planned, taught and evaluated in order to get students involved in this experience, which they discussed the importance, the technique and the inter personal relationship. The findings were obtained through observations and students’ accounts. The results were organized in categories and showed that the learning experience is rich for both students and teachers. it also showed to be interactive and helpful to the student’s knowledge. Finally we found that the use of participatory method is important to students and teachers, and contributes to a relevant learning.